Coated cutting tools
By adopting an alternate laminated structure on the cutting tool, combined with a multi-layer structure of Ti(CaN1-a) and (TixAl1-x) (CyN1-y), the problem of insufficient wear resistance and defect resistance in the prior art is solved, and the tool life is extended.
Patent Information
- Application Number
- CN202210420724.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-18
- Filing Date
- 2022-04-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-04-21
AI Technical Summary
In cutting processing, it is difficult for the prior art to simultaneously improve the wear resistance and defect resistance of cutting tools, resulting in a shortening of tool life.
A cladding layer with an alternating laminated structure is adopted. The first layer is composed of Ti(CaN1-a) and the second layer is composed of (TixAl1-x) (CyN1-y). By adjusting the composition and thickness of each layer, the structural form of columnar crystals is formed to improve the hardness and toughness of the cladding layer.
It significantly improves the wear and defect resistance of cutting tools, thereby extending the tool life.
Smart Images

Figure CN115488429B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coated cutting tool. Background Art
[0002] In the past, cutting tools including super-hard alloy or cubic boron nitride (cBN) sintered bodies were widely used in cutting of steel, etc. Among them, surface-coated cutting tools including one or more layers of hard coatings such as TiN layer, TiAlN layer, etc. on the surface of super-hard alloy substrates are used in various processes because of their high versatility.
[0003] For example, Patent Document 1 proposes a surface-coated cutting tool having a hard coating layer formed on the surface of a tool substrate composed of any one of WC superhard alloy, TiCN-based cermet, and cubic boron nitride sintered body, characterized in that (a) the hard coating layer is composed of a first layer formed on the surface of the tool substrate and a second layer formed on the first layer, and the first layer satisfies the composition formula: (Ti 1-a Al a )N (wherein a is in an atomic ratio of 0.3≤a≤0.7) with an average layer thickness of 0.5 to 3.0 μm, and a Ti and Al nitride layer satisfying the composition formula: (Ti 1-b Al b )(N 1-c C c (b) the grains of the first layer and the second layer are composed of a continuous crystal growth structure in the interface region with an interface length ratio of more than 70% between the first layer and the second layer, and the continuous crystal growth structure shows the same crystal orientation, and (c) the average width of the grains of the second layer parallel to the surface of the tool substrate is 0.05 to 1.0 μm, the average height perpendicular to the surface of the tool substrate is 0.05 to 1.5 μm, and the average aspect ratio (height / width) is 1 to 10.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Publication No. 2015-160259
[0007] Technical issues
[0008] In recent years, the turning of difficult-to-cut materials such as stainless steel has tended to be faster and faster, and under the trend of more severe cutting conditions than before, it is required to further improve the wear resistance and defect resistance to extend the tool life. In the surface-coated cutting tool of the above-mentioned Patent Document 1, by increasing the Ti content of the coating layer, the grain size of the crystal becomes larger, which can improve the wear resistance, but it is difficult to extend the tool life because the defect resistance is reduced.
[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a coated cutting tool having improved wear resistance and defect resistance and a long tool life. Summary of the invention
[0010] The present inventors have repeatedly studied how to extend the tool life of coated cutting tools and have found that if the coated cutting tool has a specific structure, its wear resistance and defect resistance can be improved, resulting in an extended tool life, thereby completing the present invention.
[0011] That is, the gist of the present invention is as follows.
[0012] [1] A coated cutting tool comprising a substrate and a coating layer formed on a surface of the substrate.
[0013] The coating layer has an alternately stacked structure in which two or more first layers and second layers are alternately stacked.
[0014] The first layer is a compound layer having a composition represented by the following formula (1):
[0015] Ti(C a N 1-a ) (1)
[0016] [wherein a represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤a≤0.4]
[0017] The second layer is a compound layer having a composition represented by the following formula (2):
[0018] (Ti x Al 1-x )(C y N 1-y ) (2)
[0019] [wherein, x represents the atomic ratio of the Ti element to the total of the Ti element and the Al element, and satisfies 0.4≤x≤0.8; y represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤y≤0.4]
[0020] The average thickness of each of the first layer and the second layer in the alternating stacked structure is 3 nm or more and 300 nm or less.
[0021] The average thickness of the alternately stacked structure is 1.0 μm or more and 8.0 μm or less.
[0022] [2] The coated cutting tool according to [1], wherein the total atomic ratio of the Ti element to the total atomic ratio of the metal elements in the coating layer is 0.7 to 0.9.
[0023] [3] The coated cutting tool according to [1] or [2], wherein an average grain size of crystal grains in the alternating layered structure is 0.1 μm or more and 1.0 μm or less.
[0024] [4] The coated cutting tool according to any one of [1] to [3], wherein the structure of the alternating stacked structure is columnar crystals.
[0025] [5] The coated cutting tool according to any one of [1] to [4], wherein the coating layer has a lower layer between the substrate and the alternating layer structure,
[0026] The lower layer is a single layer or a stack of layers of a compound composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B (except for the compound composed of the composition represented by the formula (1) and the compound composed of the composition represented by the formula (2)).
[0027] The average thickness of the lower layer is 0.2 μm or more and 3.0 μm or less.
[0028] [6] The coated cutting tool according to any one of [1] to [5], wherein the coating layer has an upper layer on a surface of the alternately stacked structure opposite to the substrate,
[0029] The upper layer is a single layer or a stack of layers of a compound composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B (except for the compound composed of the composition represented by the formula (1) and the compound composed of the composition represented by the formula (2)).
[0030] The average thickness of the upper layer is 0.2 μm or more and 3.0 μm or less.
[0031] [7] The coated cutting tool according to any one of [1] to [6], wherein the average thickness of the entire coating layer is 1.0 μm to 10.0 μm.
[0032] According to the present invention, it is possible to provide a coated cutting tool having improved wear resistance and defect resistance and a long tool life. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 1 is a schematic diagram showing an example of the coated cutting tool of the present invention.
[0034] Figure 2 1 is a schematic diagram showing another example of the coated cutting tool of the present invention.
[0035] Figure 3 This is a supplementary diagram for explaining a method for determining the aspect ratio of particles in an alternately stacked structure.
[0036] Main component symbols
[0037] Substrate 1
[0038] Second floor 2
[0039] First layer 3
[0040] Lower layer 4
[0041] Upper layer 5
[0042] Alternating stacking structure 6
[0043] Coating layer 7
[0044] Coated cutting tools8
[0045] One of the grains used to determine the average grain size is 10
[0046] A portion of the straight line used to determine the average particle size 20
[0047] The maximum distance 30 in the direction perpendicular to the surface from the straight line 20 in the crystal grain 10
[0048] The maximum distance 40 in the crystal grain 10 from the straight line 20 toward the substrate side in the vertical direction
[0049] Long axis length 50
[0050] Substrate 60 DETAILED DESCRIPTION
[0051] Hereinafter, a specific embodiment of the present invention (hereinafter referred to as "this embodiment") is described in detail, but the present invention is not limited to the following this embodiment. The present invention can be modified in various ways without departing from the main purpose thereof. In addition, in the accompanying drawings, the same symbols are marked for the same elements, and repeated descriptions are omitted. Furthermore, unless otherwise specified, the positional relationships such as up, down, left, and right are based on the positional relationships shown in the accompanying drawings. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.
[0052] The coated cutting tool of this embodiment includes a substrate and a coating layer formed on the surface of the substrate.
[0053] The coating layer has an alternately stacked structure in which two or more first layers and second layers are alternately stacked.
[0054] The first layer is a compound layer having a composition represented by the following formula (1):
[0055] Ti(C a N 1-a ) (1)
[0056] [wherein a represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤a≤0.4]
[0057] The second layer is a compound layer having a composition represented by the following formula (2):
[0058] (Ti x Al 1-x )(C y N 1-y ) (2)
[0059] [wherein, x represents the atomic ratio of the Ti element to the total of the Ti element and the Al element, and satisfies 0.4≤x≤0.8; y represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤y≤0.4]
[0060] The average thickness of each of the first layer and the second layer in the alternately stacked structure is 3 nm or more and 300 nm or less.
[0061] The average thickness of the alternately stacked structure is 1.0 μm or more and 8.0 μm or less.
[0062] Although the specific reasons why the wear resistance and defect resistance of the coated cutting tool are improved and the tool life is extended are not clear, the present inventors believe that the reasons are as follows, but the reasons are not limited to this. That is, in the first layer forming the coating layer, Ti (C a N 1-a) is 0.1 or more, the hardness of the first layer is improved, thereby improving the wear resistance of the coated cutting tool. On the other hand, in the first layer forming the coating layer, Ti(C a N 1-a ) is 0.4 or less, the wear resistance of the coated cutting tool is improved by suppressing the refinement of the structure in the first layer, and the defect resistance of the coated cutting tool is also good. In addition, in the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is 0.4 or more, as an effect of containing Ti, the wear resistance of the coated cutting tool is improved, and further, by suppressing excessive micronization of particles in the second layer, the structure becomes columnar, and the wear resistance of the coated cutting tool is improved. On the other hand, in the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is 0.8 or less, the particle coarsening in the second layer can be suppressed, thereby suppressing the defect of the coated cutting tool caused by particle shedding. In addition, in the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is 0.1 or more, the hardness of the second layer is increased, thereby improving the wear resistance of the coated cutting tool. On the other hand, in the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is less than 0.4, the wear resistance of the coated cutting tool is improved by suppressing the refinement of the structure in the second layer, and the defect resistance of the coated cutting tool is also improved. In addition, the coated cutting tool of the present embodiment has an alternating stacking structure in which the first layer and the second layer are alternately stacked in two or more layers in the coating layer, and the growth of continuous grains under the desired composition of each layer becomes easier than when formed by a single layer. In addition, in the coated cutting tool of the present embodiment, in the coating layer, the composition of the first layer is Ti(C a N 1-a ), the second layer is composed of (Ti x Al 1-x )(C y N 1-y), thus, since the alternating stacking structure as a whole contains carbon (C), the hardness of the coating layer as a whole is improved, and the wear resistance of the coated cutting tool is improved. Furthermore, the coated cutting tool of the present embodiment has an alternating stacking structure in which the first layer and the second layer are alternately stacked in two or more layers in the coating layer, thereby suppressing the coarsening of particles in each layer, thereby improving the defect resistance of the coated cutting tool. In addition, by making the average thickness of each of the first layer and the second layer in the alternating stacking structure greater than 3nm, the toughness of the coating layer is improved by stacking, and the wear resistance and defect resistance of the coated cutting tool are improved. On the other hand, by making the average thickness of each of the first layer and the second layer in the alternating stacking structure less than 300nm, the generation of crystal nuclei in the second layer can be suppressed, the grain growth is good, the micronization of particles is suppressed, and the coarse growth of specific grains in the first layer can be suppressed, and defects starting from the detachment of particles can be suppressed. In addition, if the average thickness of the alternating stacked structure is 1.0 μm or more, the particles of each layer are appropriately coarsened, thereby improving the wear resistance of the coated cutting tool, and the defect resistance of the coated cutting tool is also good. On the other hand, if the average thickness of the alternating stacked structure is 8.0 μm or less, the defect resistance of the coated cutting tool is improved mainly because the peeling of the coating layer is suppressed, and the wear resistance of the coated cutting tool is also improved. These effects complement each other, so that the wear resistance and defect resistance of the coated cutting tool of this embodiment are improved, and the tool life is long.
[0063] The coated cutting tool of the present embodiment includes a substrate and a coating layer formed on the surface of the substrate. The substrate used in the present embodiment is not particularly limited as long as it can be used as a substrate for the coated cutting tool. Examples of substrates include superhard alloys, cermets, ceramics, cubic boron nitride sintered bodies, diamond sintered bodies, and high-speed steel. Among them, if the substrate is selected from one or more of superhard alloys, cermets, ceramics, and cubic boron nitride sintered bodies, the defect resistance of the coated cutting tool is more excellent, so it is more preferred.
[0064] In the coated cutting tool of the present embodiment, the average thickness of the coating layer as a whole is preferably not less than 1.0 μm and not more than 10.0 μm. In the coated cutting tool of the present embodiment, if the average thickness of the coating layer as a whole is not less than 1.0 μm, there is a tendency for wear resistance to be improved, and the defect resistance of the coated cutting tool also tends to be improved. In addition, in the coated cutting tool of the present embodiment, if the average thickness of the coating layer as a whole is not more than 10.0 μm, there is a tendency for defect resistance to be improved mainly due to the suppression of peeling of the coating layer. From the same point of view, the average thickness of the coating layer as a whole is preferably not less than 1.2 μm and not more than 9.0 μm, and more preferably not less than 1.4 μm and not more than 8.0 μm.
[0065] [First floor]
[0066] In the coated cutting tool of the present embodiment, the first layer is a compound layer having a composition represented by the following formula (1).
[0067] Ti(C a N 1-a ) (1)
[0068] [In the formula, a represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤a≤0.4.]
[0069] In the first layer forming the coating layer, Ti(C a N 1-a ) is 0.1 or more, the hardness of the first layer is improved, thereby improving the wear resistance of the coated cutting tool. On the other hand, in the first layer forming the coating layer, Ti(C a N 1-a ) is 0.4 or less, the wear resistance of the coated cutting tool is improved by suppressing the refinement of the structure in the first layer, and the defect resistance of the coated cutting tool is also good. From the same point of view, Ti(C a N 1-a ) is preferably not less than 0.2 and not more than 0.4.
[0070] In this embodiment, the composition of each compound layer is expressed as, for example, Ti(C 0.20 N 0.80 ), it means that the atomic ratio of C element to the total of C element and N element is 0.20, and the atomic ratio of N element to the total of C element and N element is 0.80. That is, it means that the amount of C element to the total of C element and N element is 20 atomic%, and the amount of N element to the total of C element and N element is 80 atomic%.
[0071] [Second floor]
[0072] In the coated cutting tool of the present embodiment, the second layer is a compound layer having a composition represented by the following formula (2).
[0073] (Ti x Al 1-x )(C y N 1-y ) (2)
[0074] [In the formula, x represents the atomic ratio of the Ti element to the total of the Ti element and the Al element, and satisfies 0.4≤x≤0.8; y represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤y≤0.4.]
[0075] In the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is 0.4 or more, as an effect of containing Ti, the wear resistance of the coated cutting tool is improved, and the excessive micronization of particles in the second layer is suppressed, so that the structure becomes columnar, and the wear resistance of the coated cutting tool is improved. On the other hand, in the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is 0.8 or less, the particle coarsening in the second layer can be suppressed, thereby suppressing the defect of the coated cutting tool caused by particle shedding. From the same point of view, (Ti x Al 1-x )(C y N 1-y ) is preferably 0.5 or more and 0.8 or less, and more preferably 0.5 or more and 0.7 or less. In the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is 0.1 or more, the hardness of the second layer is increased, thereby improving the wear resistance of the coated cutting tool. On the other hand, in the second layer forming the coating layer, (Ti x Al 1-x )(C y N 1-y ) is less than 0.4, the wear resistance of the coated cutting tool is improved by suppressing the refinement of the structure in the second layer, and the defect resistance of the coated cutting tool is also improved. From the same point of view, (Ti x Al 1-x )(C y N 1-y ) is preferably not less than 0.2 and not more than 0.4.
[0076] In addition, in the coated cutting tool of the present embodiment, it is preferred that the second layer is first formed on the substrate surface without forming the lower layer described below. In the coated cutting tool of the present embodiment, if the second layer is first formed on the substrate surface, there is a tendency that the adhesion between the substrate and the coating layer is improved.
[0077] In addition, the total atomic ratio of the atomic ratio of the Ti element relative to the overall atomic ratio of the metal elements in the coating layer is greater than 0.7 and less than 0.9. If the total atomic ratio of the Ti element relative to the overall atomic ratio of the metal elements in the coating layer is greater than 0.7, the ratio of the Ti element in the coating layer becomes higher, so the particle size of the particles becomes larger, and there is a tendency to improve the wear resistance of the coated cutting tool. On the other hand, if the total atomic ratio of the Ti element relative to the overall atomic ratio of the metal elements in the coating layer is less than 0.9, there is a tendency to improve the defect resistance of the coated cutting tool by suppressing the coarsening of the particles. From the same point of view, the total atomic ratio of the Ti element relative to the overall atomic ratio of the metal elements in the coating layer is preferably greater than 0.7 and less than 0.8.
[0078] [Alternating stacking structure]
[0079] The coated cutting tool of this embodiment has an alternating laminated structure in which the first layer and the second layer are alternately laminated in two or more layers in the coating layer. The coated cutting tool of this embodiment has an alternating laminated structure in which the first layer and the second layer are alternately laminated in two or more layers in the coating layer, and the growth of continuous grains at the desired composition of each layer becomes easier than when the coating layer is formed by a single layer. In addition, in the coated cutting tool of this embodiment, the composition of the first layer is Ti(C a N 1-a ), the second layer is composed of (Ti x Al 1-x )(C y N 1-y ), thus, since the alternating stacking structure as a whole contains carbon (C), the hardness of the coating layer as a whole is improved, and the wear resistance of the coated cutting tool is improved. Furthermore, the coated cutting tool of this embodiment has an alternating stacking structure in which the first layer and the second layer are alternately stacked in two or more layers in the coating layer, thereby suppressing the coarsening of particles in each layer, thereby improving the defect resistance of the coated cutting tool.
[0080] In addition, in the coated cutting tool of the present embodiment, the average thickness of each layer of the first layer and the second layer is 3 nm or more and 300 nm or less. By making the average thickness of each layer of the first layer and the second layer in the alternating stacking structure 3 nm or more, the toughness of the coating layer is improved by stacking, and the wear resistance and defect resistance of the coated cutting tool are improved. On the other hand, by making the average thickness of each layer of the first layer and the second layer in the alternating stacking structure 300 nm or less, the generation of crystal nuclei in the second layer can be suppressed, the grain growth is good, the micronization of particles can be suppressed, and the coarse growth of specific grains in the first layer can be suppressed, and the defects starting from the falling of particles can be suppressed. From the same point of view, the average thickness of each layer of the first layer and the second layer is preferably 5 nm or more and 250 nm or less, and more preferably 10 nm or more and 250 nm or less.
[0081] In addition, the average thickness of each of the first layer and the second layer may be the same or different.
[0082] In addition, in the coated cutting tool of the present embodiment, the average thickness of the alternating stacked structure is greater than 1.0 μm and less than 8.0 μm. When the average thickness of the alternating stacked structure is greater than 1.0 μm, the wear resistance of the coated cutting tool is improved by coarsening the particles of each layer, and the defect resistance of the coated cutting tool is also good. On the other hand, if the average thickness of the alternating stacked structure is less than 8.0 μm, the defect resistance of the coated cutting tool is improved mainly because the peeling of the coating layer is suppressed, and the wear resistance of the coated cutting tool is also improved. From the same point of view, the average thickness of the alternating stacked structure is preferably greater than 1.2 μm and less than 6.0 μm, and more preferably greater than 1.4 μm and less than 4.2 μm.
[0083] In addition, in the coated cutting tool of the present embodiment, the average particle size of the grains in the alternating stacking structure is preferably 0.1 μm or more and 1.0 μm or less. When the average particle size of the grains in the alternating stacking structure is 0.1 μm or more, there is a tendency for the wear resistance of the coated cutting tool to improve due to the coarsening of the particles. On the other hand, when the average particle size of the grains in the alternating stacking structure is 1.0 μm or less, it is possible to suppress defects caused by particle shedding. From the same point of view, the average particle size of the grains in the alternating stacking structure is preferably 0.1 μm or more and 0.9 μm or less, and more preferably 0.2 μm or more and 0.8 μm or less.
[0084] In addition, in the present embodiment, the average particle size of the grains in the alternating stacking structure is a value obtained by drawing a line in a direction parallel to the surface of the substrate in a photograph of the sample and dividing the length of the line by the number of grains present on the line. Specifically, the average particle size of the grains in the alternating stacking structure can be measured by the method described in the embodiments described later. In addition, the grains in the alternating stacking structure include any one of the grains of the compound composed of the composition represented by formula (1) and the grains of the compound composed of the composition represented by formula (2), or include both the grains of the compound composed of the composition represented by formula (1) and the grains of the compound composed of the composition represented by formula (2).
[0085] The coated cutting tool of this embodiment preferably has a columnar crystal structure in the alternating layer structure. If the columnar crystal structure in the alternating layer structure is a columnar crystal, chipping wear can be suppressed, so the wear resistance of the coated cutting tool tends to be improved.
[0086] In this embodiment, the grains in the alternating stacking structure have an aspect ratio of 1.2 or more, which is a columnar crystal. The upper limit of the aspect ratio of the grains in the alternating stacking structure is not particularly limited, but is, for example, 4.0 or less in consideration of the thickness of the alternating stacking.
[0087] In addition, in the present embodiment, the aspect ratio can be measured by the method described in Examples described later.
[0088] In the coated cutting tool of the present embodiment, the number of repetitions of the first layer and the second layer in the alternately stacked structure is preferably 2 to 400 times, more preferably 5 to 300 times, and further preferably 7 to 200 times.
[0089] In addition, in the present embodiment, when the first layer and the second layer are formed by one layer each, the “number of repetitions” is one.
[0090] Figure 1 1 is a cross-sectional schematic diagram showing an example of a coated cutting tool of the present embodiment. The coated cutting tool 8 includes a substrate 1 and a coating layer 7 formed on the surface of the substrate 1. The coating layer 7 has a lower layer 4, an alternating stacked structure 6, and an upper layer 5 from the substrate 1 side. In addition, in the alternating stacked structure 6, the second layer 2 and the first layer 3 are alternately and repeatedly formed three times.
[0091] Figure 2 2 is a schematic cross-sectional view showing another example of the coated cutting tool of the present embodiment. The coated cutting tool 8 includes a substrate 1 and a coating layer 7 formed on the surface of the substrate 1. The coating layer 7 has an alternating laminated structure in which the second layer 2 and the first layer 3 are alternately and repeatedly formed six times starting from the substrate 1 side.
[0092] [Upper layer]
[0093] The coating layer used in this embodiment may also have an upper layer on the surface of the alternately stacked structure on the opposite side of the substrate. The upper layer is preferably a single layer or a laminate of a compound composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B (except for a compound composed of a composition represented by formula (1) and a compound composed of a composition represented by formula (2)). If the upper layer is a single layer or a laminate of such a compound, the wear resistance is more excellent, so it is more preferred. In addition, from the same viewpoint as above, the upper layer more preferably contains a compound composed of at least one element selected from Ti, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B (wherein, the compound composed of the composition represented by formula (1) and the compound composed of the composition represented by formula (2) are excluded), and further preferably contains a compound composed of at least one element selected from Ti, Nb, Ta, Cr, W, Al, Si and Y and N, and particularly preferably contains a compound composed of at least one element selected from Ti, Cr, Al and Si and N. The specific compound contained in the upper layer is not particularly limited, and examples thereof include TiAlN, AlCrN, TiSiN, etc. In addition, the upper layer may be either a single layer or a multilayer (laminated layer) of two or more layers.
[0094] In the coating layer used in the present embodiment, the average thickness of the upper layer is preferably 0.2 μm or more and 3.0 μm or less. When the average thickness of the upper layer is 0.2 μm or more, there is a tendency for the wear resistance of the coated cutting tool to be improved. On the other hand, if the average thickness of the upper layer is 3.0 μm or less, there is a tendency for the defect resistance of the coated cutting tool to be improved mainly due to the suppression of the peeling of the coating layer. From the same point of view, the average thickness of the upper layer is more preferably 0.3 μm or more and 2.0 μm or less, and more preferably 0.5 μm or more and 1.5 μm or less.
[0095] [Lower layer]
[0096] The coating layer used in the present embodiment preferably has a lower layer between the substrate and the laminated structure of the first layer and the second layer. This tends to further improve the adhesion between the substrate and the coating layer. Among them, from the same viewpoint as above, the lower layer preferably contains a compound composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B (excluding compounds composed of the composition represented by formula (1) and compounds composed of the composition represented by formula (2)), more preferably contains a compound composed of at least one element selected from Ti, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B (excluding compounds composed of the composition represented by formula (1) and compounds composed of the composition represented by formula (2)), further preferably contains a compound composed of at least one element selected from Ti, Ta, Cr, W, Al, Si and Y and N, and particularly preferably contains a compound composed of at least one element selected from Ti, Al and Si and N. The specific compound contained in the lower layer is not particularly limited, and examples thereof include TiN, TiAlN, and TiAlSiN. In addition, the lower layer may be a single layer or a plurality of layers.
[0097] In the coating layer used in the present embodiment, the average thickness of the lower layer is preferably 0.2 μm or more and 3.0 μm or less. If the average thickness of the lower layer is 0.2 μm or more, there is a tendency to improve the wear resistance of the coated cutting tool. On the other hand, if the average thickness of the lower layer is 3.0 μm or less, there is a tendency to improve the defect resistance mainly due to the suppression of the peeling of the coating layer. From the same point of view, the average thickness of the lower layer is more preferably 0.3 μm or more and 1.0 μm or less, and more preferably 0.3 μm or more and 0.5 μm or less.
[0098] [Method for producing coating layer]
[0099] The manufacturing method of the coating layer in the coated cutting tool of the present embodiment is not particularly limited, and for example, physical vapor deposition methods such as ion plating, arc ion plating, sputtering and ion mixing methods can be cited. If the coating layer is formed by physical vapor deposition, a sharp edge can be formed, so it is more preferred. Among them, the arc ion plating method makes the adhesion between the coating layer and the substrate more excellent, so it is more preferred.
[0100] [Method for manufacturing coated cutting tool]
[0101] The method for producing the coated cutting tool of the present embodiment will be described below using a specific example. The method for producing the coated cutting tool of the present embodiment is not particularly limited as long as the configuration of the coated cutting tool can be achieved.
[0102] First, the substrate processed into a tool shape is placed in a reaction container of a physical vapor deposition device, and a metal evaporation source is set in the reaction container. Then, the reaction container is evacuated to a pressure of 1.0×10 -2 Pa vacuum, and use the heater in the reaction container to heat the substrate to a temperature of 200°C to 700°C. After heating, Ar gas is introduced into the reaction container to make the pressure in the reaction container 0.5Pa to 5.0Pa. In an Ar gas atmosphere with a pressure of 0.5Pa to 5.0Pa, a bias voltage of -500V to -350V is applied to the substrate, and a current of 40A to 50A is passed through the tungsten filament in the reaction container to perform ion bombardment treatment on the surface of the substrate using Ar gas. After the ion bombardment treatment is performed on the surface of the substrate, the reaction container is evacuated until the pressure becomes 1.0×10 -2 Vacuum below Pa.
[0103] When forming the lower layer used in this embodiment, the substrate is heated to a temperature of 400° C. to 700° C. After heating, a gas is introduced into the reaction container so that the pressure in the reaction container is 0.5 Pa to 5.0 Pa. As the gas, for example, when the lower layer contains a compound composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and N, N can be listed. 2 When the lower layer contains a compound composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and N and C, N 2 Gas and C 2 H 2 The volume ratio of the mixed gas is not particularly limited, and can be, for example, N 2 Gas: C 2 H 2 Gas = 95:5 to 85:15. Next, a bias voltage of -80V to -40V is applied to the substrate, and a metal evaporation source corresponding to the metal component of each layer is evaporated by arc discharge at an arc current of 100A to 200A to form a lower layer.
[0104] When forming the first layer used in this embodiment, the temperature of the substrate is controlled to be 300° C. to 800° C. 2 H 2 and N 2 The mixed gas of the gases is introduced into the reaction container so that the pressure in the reaction container is 1.0 Pa to 10.0 Pa. The volume ratio of the mixed gas is not particularly limited, and can be, for example, C 2 H 2Gas: N 2 Gas = 3:97 to 25:75. Then, a bias voltage of -200 V to -40 V is applied to the substrate, and an arc discharge of 80 A to 200 A is used to evaporate the Ti evaporation source to form the first layer.
[0105] When forming the second layer used in this embodiment, the substrate is controlled to have a temperature of 300°C to 800°C. In addition, if the substrate temperature is made the same as the substrate temperature when the first layer is formed, the first layer and the second layer can be formed continuously, which is more preferable. 2 H 2 Gas and N 2 The mixed gas of the gases is introduced into the reaction container so that the pressure in the reaction container is 1.0 Pa to 10.0 Pa. The volume ratio of the mixed gas is not particularly limited, and can be, for example, C 2 H 2 Gas: N 2 Gas = 3:97 to 25:75. Next, a bias voltage of -200 V to -40 V is applied to the substrate, and an arc discharge with an arc current of 80 A to 200 A is performed to evaporate a metal evaporation source corresponding to the metal component of the second layer to form the second layer.
[0106] In order to form an alternating stacked structure in which two or more first layers and second layers are alternately stacked, the Ti evaporation source and the metal evaporation source are alternately evaporated by arc discharge under the above conditions to alternately form each layer. The thickness of each layer constituting the alternating stacked structure can be controlled by adjusting the arc discharge time of the Ti evaporation source and the metal evaporation source respectively.
[0107] When forming the first layer, if C is increased 2 H 2 If the ratio of the gas is increased, the ratio of the N element in the composition shown in formula (1) becomes smaller, and the ratio of the C element can be increased (a). 2 H 2 If the ratio of the gas is increased, in the composition shown in formula (2), the ratio of the N element becomes smaller and the ratio of the C element (y) can be increased.
[0108] In order to make the average grain size of the grains in the alternating stacking structure used in the present embodiment a specified value, in the process of forming the above-mentioned alternating stacking structure, the thickness of each layer in the alternating stacking structure, the ratio of the Ti element in the alternating stacking structure, the ratio of the C element in the first layer and / or the second layer, the thickness of the second layer, and the negative bias voltage can be adjusted. More specifically, if the thickness of each layer in the alternating stacking structure is reduced, the average grain size of the grains in the alternating stacking structure tends to become smaller. In addition, if the ratio of the Ti element in the alternating stacking structure is reduced, the average grain size of the grains in the alternating stacking structure tends to become smaller. In addition, if the ratio of the C element in the first layer and / or the second layer is increased, the average grain size of the grains in the alternating stacking structure tends to become smaller. In addition, if the thickness of the second layer is increased, the average grain size of the grains in the alternating stacking structure tends to become smaller. In addition, if the negative bias voltage (away from the zero side) is increased, there is a tendency for the average grain size of the grains in the alternating stacking structure to become smaller.
[0109] In order to make the atomic ratio of the total atomic ratio of the Ti element relative to the overall atomic ratio of the metal elements in the coating layer used in this embodiment a predetermined value, in the process of forming the above-mentioned alternating stacked structure, the thickness of each layer in the alternating stacked structure and the ratio of the Ti element in the second layer can be adjusted. More specifically, if the thickness of the first layer in the alternating stacked structure is increased (the proportion of the first layer is increased), the atomic ratio of the total atomic ratio of the Ti element relative to the overall atomic ratio of the metal elements in the coating layer tends to increase. In addition, if the ratio of the Ti element in the second layer is increased, the atomic ratio of the total atomic ratio of the Ti element relative to the overall atomic ratio of the metal elements in the coating layer tends to increase.
[0110] In order to make the organizational morphology of the alternating stacked structure used in the present embodiment columnar crystal, that is, to make the aspect ratio of the grains in the alternating stacked structure greater than 1.2, the average grain size of the grains in the alternating stacked structure and the average thickness in the alternating stacked structure can be adjusted during the formation of the alternating stacked structure. More specifically, if the average grain size of the grains in the alternating stacked structure is reduced, there is a tendency for the aspect ratio of the grains in the alternating stacked structure to increase. In addition, if the average thickness in the alternating stacked structure is increased, there is a tendency for the aspect ratio of the grains in the alternating stacked structure to increase.
[0111] When forming the upper layer used in the present embodiment, it can be formed under the same manufacturing conditions as the above-mentioned lower layer. That is, first, the substrate is heated to a temperature of 400°C to 700°C. After heating, a gas is introduced into the reaction container so that the pressure in the reaction container is 0.5Pa to 5.0Pa. As the gas, for example, when the upper layer contains at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and N constitutes a compound, N can be listed. 2 When the upper layer contains at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and a compound composed of N and C, N 2 Gas and C 2 H 2 The volume ratio of the mixed gas is not particularly limited, and can be, for example, N 2 Gas: C 2 H 2 Gas = 95:5 to 85:15. Next, a bias voltage of -80V to -40V is applied to the substrate, and an arc discharge with an arc current of 100A to 200A is performed to evaporate a metal evaporation source corresponding to the metal component of each layer to form an upper layer.
[0112] The thickness of each layer constituting the coating layer in the coated cutting tool of the present embodiment can be measured based on the cross-sectional structure of the coated cutting tool using an optical microscope, a scanning electron microscope (SEM), a transmission electron microscope (TEM), etc. In addition, the average thickness of each layer in the coated cutting tool of the present embodiment can be obtained by measuring the thickness of each layer at three or more cross sections near a position moved 50 μm from the blade edge line portion of the surface opposite to the metal evaporation source to the center of the surface, and calculating the average value (arithmetic mean).
[0113] In addition, the composition of each layer constituting the coating layer in the coated cutting tool of this embodiment can be measured based on the cross-sectional structure of the coated cutting tool of this embodiment using an energy dispersive X-ray analyzer (EDS) or a wavelength dispersive X-ray analyzer (WDS).
[0114] It is understood that the coated cutting tool of the present embodiment can extend the tool life compared with the past due to at least excellent wear resistance and defect resistance (wherein, the reason for extending the tool life is not limited to the above content). As the types of the coated cutting tool of the present embodiment, specifically, a head-replaceable cutting insert for milling or turning, a drill, and an end mill, etc. can be listed.
[0115] [Example]
[0116] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0117] (Example 1)
[0118] As a substrate, a CNMG120408-TSF insert (manufactured by TUNGALOY Co., Ltd.) (having 54.0% Ti(C, N)-22.5% WC-6.8% NbC-1.0% Mo) was prepared. 2 C-0.7% ZrC-7.5% Co-7.5% Ni (the above are mass %) superhard alloy. A Ti evaporation source and a metal evaporation source are arranged in the reaction vessel of the arc ion plating device to obtain the composition of each layer as shown in Table 1. The prepared substrate is fixed to the fixing parts of the rotating table in the reaction vessel.
[0119] Then, the reaction container was evacuated to a pressure of 5.0×10 -3 After evacuation, the substrate was heated to 450° C. by a heater in the reaction container. After heating, Ar gas was introduced into the reaction container to a pressure of 2.7 Pa.
[0120] In an Ar gas atmosphere with a pressure of 2.7 Pa, a bias voltage of -400 V was applied to the substrate, and a current of 40 A was passed through the tungsten filament in the reaction container, and the surface of the substrate was subjected to ion bombardment treatment using Ar gas for 30 minutes. After the ion bombardment treatment was completed, the reaction container was evacuated to a pressure of 5.0×10 -3 Vacuum below Pa.
[0121] For the invention products 1 to 21, after evacuation, the temperature of the substrate was controlled to be the temperature shown in Table 2 (temperature at the start of film formation), and the C 2 H 2 Gas and N 2 The gas mixture is mixed at the volume ratio shown in Table 2, introduced into the reaction container, and the pressure in the reaction container is adjusted to the pressure shown in Table 2. After that, the bias voltage shown in Table 2 is applied to the substrate, and the Ti evaporation source of the first layer of the composition shown in Table 1 and the metal evaporation source of the second layer of the composition shown in Table 1 are alternately evaporated by arc discharge with the arc current shown in Table 2 in the order that the bottom layer shown in Table 1 is formed first on the surface of the substrate, and the first layer and the second layer are alternately formed to form an alternating stacked structure. At this time, control is performed to achieve the pressure in the reaction container shown in Table 2. In addition, the respective arc discharge times are controlled and adjusted so that the thickness of the first layer, the thickness of the second layer, and the thickness of the alternating stacked structure become the thicknesses shown in Table 1.
[0122] For Comparative Products 1 to 12, after evacuation, the substrate was controlled to have a temperature shown in Table 2 (temperature at the start of film formation), the pressure in the reaction container was adjusted to the pressure shown in Table 2, and the gas was introduced into the reaction container. 2 H 2 Gas and N 2 The mixed gas of the gases was mixed in the volume ratio shown in Table 2 and introduced into the reaction container. For Comparative Product 2, N 2 The gas is introduced into the reaction container. After that, the bias voltage shown in Table 2 is applied to the substrate, and the arc discharge with the arc current shown in Table 2 is used to alternately evaporate the Ti evaporation source of the first layer of the composition shown in Table 1 and the metal evaporation source of the second layer of the composition shown in Table 1 in the order that the bottom layer is first formed on the substrate surface, so as to alternately form the first layer and the second layer, thereby forming an alternating stacking structure. At this time, the pressure in the reaction container is controlled to be the pressure shown in Table 2. In addition, the arc discharge time is controlled and adjusted so that the thickness of the first layer, the thickness of the second layer, and the thickness of the alternating stacking structure become the thickness shown in Table 1.
[0123] After each layer and the laminated structure were formed on the substrate surface to a predetermined average thickness as shown in Table 1, the power of the heater was turned off, and after the sample temperature reached 100° C. or less, the sample was taken out from the reaction container.
[0124] [Table 1]
[0125]
[0126] [Table 2]
[0127]
[0128] [Average thickness]
[0129] TEM observation was performed on three cross sections at a position of 50 μm from the edge line of the blade of the surface of the coated cutting tool facing the metal evaporation source toward the center of the surface, and the thickness of each layer was measured and the average value (arithmetic mean) was calculated, thereby obtaining the average thickness of each layer of the obtained sample. These results are shown in Table 1.
[0130] [Composition of each layer]
[0131] In the cross section near the position of 50 μm moved from the cutting edge ridge of the surface of the coated cutting tool opposite to the metal evaporation source to the center, the composition of each layer of the obtained sample was measured using EDS matched with TEM. The measurement results are shown in Table 1. In addition, the composition ratio of the metal elements of each layer in Table 1 represents the atomic ratio of each metal element relative to the overall metal element in the metal compound constituting each layer. In addition, based on the measurement results of the composition of each layer, the total atomic ratio of the atomic ratio of the Ti element relative to the overall metal element in the coating layer is calculated. The results are shown in Table 3.
[0132] [Average particle size, structure morphology and aspect ratio]
[0133] For the obtained sample, as described below, a commercially available transmission microscope (TEM) is used to measure the average particle size of the grains in the alternating stacking structure. First, a focused ion beam (FIB) processing machine is used to prepare a thin film sample with a cross section in the alternating stacking structure of the coating layer (a cross section in the same direction as when observing the thickness of the coating layer: a direction perpendicular to the surface of the substrate) as the observation surface. A scanning transmission electron image (STEM image) is taken of the observation surface of the prepared sample. At a position of 80% of the thickness of the alternating stacking structure from the substrate side to the surface side of the photograph taken, a straight line is drawn in a direction parallel to the surface of the substrate, and the number of grains present on the line is measured. The value obtained by dividing the length of the straight line by the number of grains present on the line is used as the average particle size of the grains in the alternating stacking structure. At this time, the length of the straight line is greater than 10μm.
[0134] In addition, the aspect ratio of particles in the alternating stacked structure is calculated as follows. Figure 3 As shown, in one of the crystal grains 10 used in the measurement of the average grain size, the sum of the maximum distance 30 in the perpendicular direction from the straight line 20 toward the surface side and the maximum distance 40 in the perpendicular direction from the straight line 20 toward the substrate side is taken as the length 50 of the major axis. Similarly, the length of the major axis of each crystal grain used in the measurement of the average grain size is obtained, and the value obtained by dividing the average value of the lengths of the major axes by the average grain size is taken as the aspect ratio of the particles in the alternately stacked structure.
[0135] In addition, the structure morphology in the alternating layer structure was determined based on the photographs of the observation surface.
[0136] [Table 3]
[0137]
[0138] The obtained samples were used to perform the following cutting tests 1 and 2 and evaluate them.
[0139] [Cutting test 1 (wear resistance test)]
[0140] Cutting material: S45C
[0141] Cutting material shape: S45C round bar
[0142] Cutting speed: 250m / min
[0143] Feed per edge: 1.0mm / rev
[0144] Cutting depth: 0.2mm
[0145] Coolant: Use
[0146] Evaluation items: The tool life is defined as the time when the flank wear width of the sample reaches 0.2 mm or when the sample is broken (a notch is formed on the cutting edge of the sample). The machining time until the tool life is measured. The longer the machining time until the tool life is, the better the wear resistance is evaluated to be.
[0147] [Cutting test 2 (fracture resistance test)]
[0148] Cutting material: S45C
[0149] Shape of the material being cut: Round bar with a groove on the side of S45C
[0150] Cutting speed: 150m / min
[0151] Feed per edge: 1.0mm / rev
[0152] Cutting depth: 0.1mm
[0153] Coolant: Use
[0154] Evaluation items: The time when the sample is chipped is regarded as the tool life, and the number of impacts until the tool life is measured. In addition, the number of impacts is the number of times the sample contacts the cut material, and the test is terminated when the sample is chipped. The greater the number of impacts until the tool life, the better the chipping resistance is evaluated.
[0155] For the machining time until the tool life of cutting test 1 (wear resistance test), 40 minutes or more was evaluated as "A", 30 minutes or more and less than 40 minutes was evaluated as "B", and less than 30 minutes was evaluated as "C". In addition, for the number of impacts until the tool life of cutting test 2 (defect resistance test), 3000 times or more was evaluated as "A", 2000 times or more and less than 3000 times was evaluated as "B", and less than 2000 times was evaluated as "C". In this evaluation, "A" is the best, "B" is the second best, and "C" means the worst. The more A or B, the better the cutting performance. The obtained evaluation results are shown in Table 4.
[0156] [Table 4]
[0157]
[0158] As shown in the results in Table 4, the evaluations of the cutting test 1 (wear resistance test) and the cutting test 2 (fracture resistance test) of the product of the present invention were both "B" or higher. On the other hand, in the evaluation of the comparative product, both or either of the cutting test 1 (wear resistance test) and the cutting test 2 (fracture resistance test) were "C". Therefore, it can be seen that the wear resistance and fracture resistance of the product of the present invention are generally superior to those of the comparative product.
[0159] From the above results, it is understood that the product of the present invention is excellent in wear resistance and defect resistance, and thus has a long tool life.
[0160] (Example 2)
[0161] As a substrate, a CNMG120408-TSF insert (manufactured by TUNGALOY Co., Ltd.) (having 54.0% Ti(C, N)-22.5% WC-6.8% NbC-1.0% Mo) was prepared. 2 C-0.7% ZrC-7.5% Co-7.5% Ni (the above are mass %) superhard alloy. A Ti evaporation source and a metal evaporation source are arranged in the reaction vessel of the arc ion plating device to obtain the composition of each layer as shown in Table 5. The prepared substrate is fixed to the fixing parts of the rotating table in the reaction vessel.
[0162] Then, the reaction container was evacuated to a pressure of 5.0×10 -3 After evacuation, the substrate was heated to 450° C. by a heater in the reaction container. After heating, Ar gas was introduced into the reaction container to a pressure of 2.7 Pa.
[0163] In an Ar gas atmosphere with a pressure of 2.7 Pa, a bias voltage of -400 V was applied to the substrate, and a current of 40 A was passed through the tungsten filament in the reaction container, and the surface of the substrate was subjected to ion bombardment treatment using Ar gas for 30 minutes. After the ion bombardment treatment was completed, the reaction container was evacuated to a pressure of 5.0×10 -3 Vacuum below Pa.
[0164] For the invention products 21 to 25, after evacuation, the substrate was heated to a temperature shown in Table 6 (temperature at the start of film formation), and N 2The gas was introduced into the reaction container, and the pressure in the reaction container was adjusted to the pressure shown in Table 6. Then, the bias voltage shown in Table 6 was applied to the substrate, and the metal evaporation source having the composition shown in Table 5 was evaporated by arc discharge with the arc current shown in Table 6 to form the lower layer.
[0165] Next, for invention product 21, the manufacturing conditions for the alternating stacking structure are the same as those of invention product 1, for invention product 22, the manufacturing conditions for the alternating stacking structure are the same as those of invention product 16, for invention product 23, the manufacturing conditions for the alternating stacking structure are the same as those of invention product 17, for invention product 24, the manufacturing conditions for the alternating stacking structure are the same as those of invention product 18, and for invention product 25, the manufacturing conditions for the alternating stacking structure are the same as those of invention product 19, a first layer and a second layer are alternately formed on the surface of the lower layer to form an alternating stacking structure.
[0166] Next, for the invention products 21 to 23, after evacuation, the substrate was heated to a temperature shown in Table 7 (temperature at the start of film formation), and N 2 The gas was introduced into the reaction container, and the pressure in the reaction container was adjusted to the pressure shown in Table 7. Then, the bias voltage shown in Table 7 was applied to the substrate, and the metal evaporation source having the composition shown in Table 5 was evaporated by arc discharge with the arc current shown in Table 7 to form an upper layer.
[0167] After each layer was formed on the substrate surface to a predetermined average thickness as shown in Table 5, the power of the heater was turned off, and after the sample temperature reached 100° C. or less, the sample was taken out from the reaction container.
[0168] [Table 5]
[0169]
[0170] [Table 6]
[0171]
[0172] [Table 7]
[0173]
[0174] [Average thickness]
[0175] TEM observation was performed on three cross sections at a position 50 μm away from the edge line of the blade of the surface of the coated cutting tool facing the metal evaporation source toward the center of the surface, and the thickness of each layer was measured and the average value (arithmetic mean) was calculated, thereby obtaining the average thickness of each layer of the obtained sample. These results are shown in Table 5.
[0176] [Composition of each layer]
[0177] In the cross section near the position of 50 μm moved from the cutting edge ridge of the surface of the coated cutting tool opposite to the metal evaporation source to the center, the composition of each layer of the obtained sample was measured using EDS matched with TEM. The measurement results are shown in Table 5. In addition, the composition ratio of the metal elements of each layer in Table 1 represents the atomic ratio of each metal element relative to the overall metal element in the metal compound constituting each layer. In addition, based on the measurement results of the composition of each layer, the total atomic ratio of the atomic ratio of the Ti element relative to the overall metal element in the coating layer is calculated. The results are shown in Table 8.
[0178] [Average particle size, structure morphology and aspect ratio]
[0179] For the obtained sample, as described below, a commercially available transmission microscope (TEM) is used to measure the average particle size of the grains in the alternating stacking structure. First, a focused ion beam (FIB) processing machine is used to prepare a thin film sample with a cross section in the alternating stacking structure of the coating layer (a cross section in the same direction as when observing the thickness of the coating layer: a direction perpendicular to the surface of the substrate) as the observation surface. A scanning transmission electron image (STEM image) is taken of the observation surface of the prepared sample. At a position of 80% of the thickness of the alternating stacking structure from the substrate side to the surface side of the photograph taken, a straight line is drawn in a direction parallel to the surface of the substrate, and the number of grains present on the line is measured. The value obtained by dividing the length of the straight line by the number of grains present on the line is used as the average particle size of the grains in the alternating stacking structure. At this time, the length of the straight line is greater than 10μm.
[0180] In addition, the aspect ratio of particles in the alternating stacked structure is calculated as follows. Figure 3 As shown, in one of the crystal grains 10 used in the measurement of the average grain size, the sum of the maximum distance 30 in the perpendicular direction from the straight line 20 toward the surface side and the maximum distance 40 in the perpendicular direction from the straight line 20 toward the substrate side is taken as the length 50 of the major axis. Similarly, the length of the major axis of each crystal grain used in the measurement of the average grain size is obtained, and the value obtained by dividing the average value of the lengths of the major axes by the average grain size is taken as the aspect ratio of the particles in the alternately stacked structure.
[0181] In addition, the structure morphology in the alternating layer structure was determined based on the photographs of the observation surface.
[0182] [Table 8]
[0183]
[0184] Using the obtained samples, the same cutting tests 1 and 2 as in Example 1 were carried out and evaluated.
[0185] For the machining time until the tool life of cutting test 1 (wear resistance test), 40 minutes or more was evaluated as "A", 30 minutes or more and less than 40 minutes was evaluated as "B", and less than 30 minutes was evaluated as "C". In addition, for the number of impacts until the tool life of cutting test 2 (defect resistance test), 3000 times or more was evaluated as "A", 2000 times or more and less than 3000 times was evaluated as "B", and less than 2000 times was evaluated as "C". In this evaluation, "A" is the best, "B" is the second best, and "C" means the worst. The more A or B, the better the cutting performance. The obtained evaluation results are shown in Table 9.
[0186] [Table 9]
[0187]
[0188] From the results shown in Table 9, it can be seen that the evaluations of the cutting test 1 (wear resistance test) and the cutting test 2 (fracture resistance test) of the invention product were both "B" or higher. Therefore, it can be seen that the invention product has excellent wear resistance and fracture resistance even if it has an upper layer and / or a lower layer, and the tool life is long.
[0189]
Industrial Applicability
[0190] The coated cutting tool of the present invention is excellent in wear resistance and defect resistance, and thus can extend the tool life compared to conventional ones, and in this respect has high industrial applicability.
Claims
1. A coated cutting tool comprising a substrate and a coating layer formed on a surface of the substrate, The coating layer has an alternately stacked structure in which two or more first layers and second layers are alternately stacked. The first layer is a compound layer having a composition represented by the following formula (1): You(C a N 1-a )(1) In formula (1), a represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤a≤0.4; The second layer is a compound layer having a composition represented by the following formula (2): (You x To the 1-x )(C y N 1-y )(2) In formula (2), x represents the atomic ratio of the Ti element to the total of the Ti element and the Al element, and satisfies 0.4≤x≤0.8; y represents the atomic ratio of the C element to the total of the C element and the N element, and satisfies 0.1≤y≤0.4; The average thickness of each of the first layer and the second layer in the alternating stacked structure is 3 nm or more and 300 nm or less. The average thickness of the alternating stacked structure is not less than 1.0 μm and not more than 8.0 μm; The average grain size of the crystal grains in the alternating stacked structure is 0.1 μm or more and 1.0 μm or less.
2. The coated cutting tool according to claim 1, wherein: The total atomic ratio of the Ti element to the total atomic ratio of the metal elements in the coating layer is 0.7 to 0.
9.
3. The coated cutting tool according to claim 1 or 2, wherein: The organizational morphology in the alternating stacked structure is columnar crystals.
4. The coated cutting tool according to claim 1 or 2, wherein: The cladding layer has a lower layer between the substrate and the alternating stacked structure, The lower layer is a single layer or a stack of compounds composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B, excluding the compound composed of the composition represented by the formula (1) and the compound composed of the composition represented by the formula (2). The average thickness of the lower layer is 0.2 μm or more and 3.0 μm or less.
5. The coated cutting tool according to claim 1 or 2, wherein: The coating layer has an upper layer on the surface of the alternately stacked structure on the side opposite to the substrate. The upper layer is a single layer or a stack of compounds composed of at least one element selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si and Y, and at least one element selected from C, N, O and B, excluding the compound composed of the composition represented by the formula (1) and the compound composed of the composition represented by the formula (2). The average thickness of the upper layer is 0.2 μm or more and 3.0 μm or less.
6. The coated cutting tool according to claim 1 or 2, wherein: The average thickness of the entire coating layer is 1.0 μm or more and 10.0 μm or less.
Citation Information
Patent Citations
Surface-coated cutting tool excellent in abrasion resistance
JP2015160259A
Coated cutting tool
CN109304489A
Tough composite multilayer-coated tool
JP1999222665A